Schultz and Modified Schultz Polynomials of Edges Induce Chain and Ring for Hexagonal Graphs (European Journal of Pure and Applied Mathematics, 2023)
Schultz polynomial is one of the must significant formulas that represent a relationship between the degree’s of vertices in a simple connected graph G and the distances between these vertices. In this work, Schultz and modified Schultz polynomials, as well as their topological indices of chain and ring hexagonal graphs, have been successfully identified.
Keywords: Schultz polynomials; Modified Schultz polynomials; chains hexagonal; ring hexagonal